Sustainable consumption: The new economics and local organic food - Gill Seyfang (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2006)
Sustainable consumption is increasingly on the policy menu, and local organic food provision has been widely advocated as a practical means of making the desired changes to conventional production and consumption systems. This paper presents the first empirical evaluation of a local organic food network as a tool for sustainable consumption. It thereby makes a timely and original contribution to the debate on environmental governance by discussing the role and potential of local organic food networks to develop new institutions which enable individuals and groups to change their consumption patterns. A new multi-criteria qualitative evaluation tool is developed, from the New Economics theory, to assess the effectiveness of initiatives at achieving sustainable consumption. The key indicators of sustainable consumption are: localisation, reducing ecological footprints, community-building, collective action, and creating new socio-economic institutions. This evaluation framework is applied to a case study organic producer cooperative in Norfolk, UK, which is found to be effective at achieving sustainable consumption, but which nevertheless faces a number of barriers. Finally, the possible ways forward for community-based sustainable consumption are discussed, together with appropriate policy recommendations.
Keywords: 330; institutions; localism; new economics; organics; sustainable consumption